2018
DOI: 10.1177/1940082918785079
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Potential Predation Risk by Introduced Predators on Unattended Eggs in the Red-Tailed Tropicbird, Phaethon rubricauda, on Rapa Nui (Easter Island)

Abstract: Anthropogenic impact has been heavy in remote oceanic islands, including the introduction of alien species, having negative effects on native seabirds. The isolated and subtropical Rapa Nui (Easter Island) is one of the few known breeding sites of the red-tailed tropicbird, Phaethon rubricauda in Chile (southeastern Pacific Ocean) where is listed as vulnerable. A relatively new breeding colony is found in the Rano Raraku volcano, where human-introduced species are present. We used hen eggs as a proxy for red-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
0
16
2
Order By: Relevance
“…Artificial nest studies comprised 29% of all experimental camera trap studies on predator–prey ecology in our literature search (Smith et al, 2020). The simplest design is to pair nests containing experimental eggs with a camera trap to monitor predator visitation and attack rates (Kämmerle, Niekrenz, & Storch, 2019; Luna, Varela, Brokordt, & Luna‐Jorquera, 2018; Patterson, Kalle, & Downs, 2016; Ponce, Salgado, Bravo, Gutiérrez, & Alonso, 2018). Additional prey cues can also supplement traditional artificial nest experiments to identify predator attractants; a study on artificial terrapin nests found that the scent of disinterred soil was a stronger attractant for predators than terrapin scent or visual cues (Buzuleciu, Crane, & Parker, 2016).…”
Section: Experimental Applications Of Camera Traps To Predator–prey Ementioning
confidence: 99%
“…Artificial nest studies comprised 29% of all experimental camera trap studies on predator–prey ecology in our literature search (Smith et al, 2020). The simplest design is to pair nests containing experimental eggs with a camera trap to monitor predator visitation and attack rates (Kämmerle, Niekrenz, & Storch, 2019; Luna, Varela, Brokordt, & Luna‐Jorquera, 2018; Patterson, Kalle, & Downs, 2016; Ponce, Salgado, Bravo, Gutiérrez, & Alonso, 2018). Additional prey cues can also supplement traditional artificial nest experiments to identify predator attractants; a study on artificial terrapin nests found that the scent of disinterred soil was a stronger attractant for predators than terrapin scent or visual cues (Buzuleciu, Crane, & Parker, 2016).…”
Section: Experimental Applications Of Camera Traps To Predator–prey Ementioning
confidence: 99%
“…The lack of differences in any of the physiological stress indicators assessed on adult birds between exposed and protected nests within the Rapa Nui colony may be explained by the absence of differences in the frequency of introduced predators visits between nests types, as found in the experiment with simulated unattended eggs in this colony ( Luna et al, 2018 ). It is worth noting that in the experiment reported in Luna et al (2018) simulated eggs were placed in empty red-tailed tropicbird nests when no birds were present in the colony. In the present study we further evaluated the potential differences between the two nest categories because the presence and behavior of introduced predators may differ widely between an active vs. an un-active colony.…”
Section: Discussionmentioning
confidence: 81%
“…The assessed colony is located at the Rano Raraku volcano in the eastern part of the island. This colony is almost free of louse flies (N. Luna, 2016, personal observation), but introduced predators are present, including rats of the genus Rattus , feral cats, feral dogs and the raptor bird chimango caracara ( Phalcoboenus chimango ) ( Flores et al, 2017 ; Luna et al, 2018 ). Two distinctive red-tailed tropicbird nest types were recognized in this colony, one covered by rocks (sometimes moais or inside caves) characterized as “protected”, and the other type covered only by grass, with little or no rocky protection, characterized as “exposed” (as describe Prys-Jones & Peet, 1980 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On Motu Nui, masked boobies nest in areas free from grass on the top of the islet and on the cliffs. Similar to Rapa Nui, Motu Nui has introduced species, including the Argentine ant (Linepithema humile) and the Chimago caracara (Phalcoboenus chimango), which can be potential predators of seabird chicks and eggs (Luna et al 2018). There were 56 breeding pairs of masked boobies in 2016 and 77 breeding pairs in 2017.…”
Section: Data Collectionmentioning
confidence: 99%